Evolutionary History and Functionality Analysis of Arogenate Dehydratases of Arabidopsis Thaliana: A Bioinformatic Approach: Evolution and Function of Arogenate Dehydratases in Arabidopsis - Akhand, Mst Rubaiat Nazneen; Akter, Hafsa; Ahmed, Jamil; Jahan, Nusrat (Journal of the Sylhet Agricultural University, 2025)
Phenylalanine is an important plant derived aromatic amino acid that acts as an integral precursor of various specialized metabolites. Shikimate pathway is considered as the fundamental route for phenylalanine biosynthesis in plants. The crucial last step of this pathway is catalyzed by arogenate dehydratase (ADT) to synthesize phenylalanine from arogenate. Arabidopsis thaliana has six copies of ADT that catalyze phenylalanine production and initiate the downstream pathway to produce a large number of secondary metabolites. However, how do the copies of ADT have been evolved in different trajectories of land plant is relatively unknown. It is also unclear whether all the copies of Arabidopsis ADT have evolved at the same rate during the course of evolution. In addition, it is unknown how the multiple copies of Arabidopsis ADT contribute towards functional complexity. Our phylogenetic study revealed that all the domains of ADT had evolved before the land plant evolution as it was found in red algae, green algae and in fungus, indicating the presence of functional ADTs in all the spectrum of plants, algae and fungi. ADTs of Arabidopsis formed four different clusters which might suggest to their functional differences. Expression analysis revealed the dominative role of ADT2 in seed development, while the rest of the ADTs showed spatiotemporal expression and contributed to other developmental functions of Arabidopsis. J. Sylhet Agril. Univ. 12(1): 16-37, 2025